ANALYSIS OF THE INFLUENCE OF GRDP, TOTAL POPULATION, WAGES, AND INFLATION ON TOTAL CONSUMPTION IN SUMATRA PROVINCE IN 2020-2023 - Friscatama Puspita Ayu H; Siti Fatimah Nurhayanti (Universitas KH. Abdul Chalim Mojokerto, 2026)
Consumption is the activity of using goods and services to meet the needs and desires of individuals or households. This study aims to analyze the effect of Gross Domestic Product, population size, minimum wage, and inflation on total consumption in North Sumatra province from 2020 to 2023. The analytical tool used is panel data regretion using secondary data obtained from the Central Bureau of Statistics during the period 2020-2023. The best model selected is the fixed effect model (FEM). Regression results show that GDP affects total consumption in North Sumatra from 2020 to 2023. Meanwhile, population size, minimum wage, and inflation do not affect total consumption in North Sumatra from 2020 to 2023.